The effect of n-H₂ impurity on the heat capacity of solid Ne - Bagatskii, M.I.; Minchina, I.Ya.; Parbuzin, V.S. (Физика низких температур, 2009)
The alloy of Ne - 5.1%n-H₂ was investigated calorimetrically under equilibrium vapor pressure in an interval of 0.9–25 K. The magnitudes and the temperatures dependencies of the heat capacity Cso₁(T) of the alloy at T = 11–20 K are strongly dependent on the conditions of sample preparation. The temperatures dependencies of the Cso₁(T) of the sample prepared in a calorimeter by direct condensation of a gas mixture at T = 15 K exhibit a smeared maximum near the triple point temperature of hydrogen and a phase transition at T = 17.1 K. The detected features of Cso₁(T) indicate that the preparation of the solid Ne – n-H₂ from a gas phase leads to the formation of a nonequilibrium long-living phase Ne with large H₂ concentrations and a small portion of H₂ inclusions with low Ne concentrations. The phase transition is caused by decompositions of this phase. The phase dose not recover on cooling the sample after the phase transition. It is found that the rate of the ortho-para conversion of the H₂ molecules in the solid Ne – n-H₂ solutions higher than that of solid H₂.